Dampak Pandemi Covid dan Penerapan New Normal pada Kredit Bermasalah dan Profitabilitas Perbankan Di Indonesia - Tri Septyanto; Dewi Susilowati (Universitas Muhammadiyah Purwokerto, 2022)
The COVID-19 pandemic has had a significant impact on the economy, and the banking industry is no exception. The impact of the pandemic on the banking industry, namely the decline in bank health. Various efforts have been made by the government to revive the banking industry, one of which is the issuance of OJK regulation Number 11/PJOK.03/2020 concerning